Fourth Industrial Revolution and the Future of Neurosurgery - Sharma, Mohan Raj; Sharma, Meghraj (Nepal Journal of Neuroscience, 2022)
Arguably, neurosurgery is the second oldest profession although it only evolved as a distinct field of surgery in the 20th century. During the last seven decades, the advent of the operating microscope, intraoperative neuro monitoring, neurointensive care, neuronavigation, and the evolution of minimally invasive and endovascular techniques have changed the landscape of neurosurgery. This editorial intends to highlight the importance of the fourth industrial revolution (Industry 4.0), its components, and how they have the prospect of being integrated into the practice of medicine, especially neurosurgery.